The Carolingian Epic in Traditional Liège Puppet Theatre: A Case Study of “Huon de Bordeaux” and “Quatre fils Aymon” (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2023)
Although Carolingian epics are at the heart of the traditional Liège puppet repertoire, they remain a little explored field of research. This essay focuses on two epics, Les quatre fils Aymon and Huon de Bordeaux, which serve as case studies to examine the transition from narrative to dramatic text and its transposition for the regional puppet stage. Following the stories from the,annotated novels to the modern plays, the first part shows how the dramatisation of the prose text gradually developed. The second part examines the creation process of staging the story of the paladins of France from the point of view of regional identification, focusing on the role of Tchantchès, the typical character of the Liège puppet theatre.
Keywords: Carolingian Epics; Liège puppet theatre; Tchantchès; Les quatre fils Aymon; Huon de Bordeaux; Children auditory; Popular puppet theatre; Regional identification; Chivalric novel